Two new records of Viola L. (Violaceae) for Nepal - Dani, Ramesh S; Shrestha, Krishna K (Himalayan Journal of Sciences, 2006)
Viola mandshurica W. Becker and Viola odorata L. belonging to the family Violaceae are reported for the first time from Nepal. The plants were collected along the trail between the suburbs Chovar and Jalbinayak, Kathmandu. Key words: Herbarium, Nepal, Viola Himalayan Journal of Sciences 2(3): 48-50, 2004